2005
DOI: 10.1111/j.1365-2400.2005.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Fishery‐specific differences in the size selectivity and catch of diamond‐ and square‐mesh codends in two Australian penaeid seines

Abstract: The selectivities and catch compositions of conventional 30-mm diamond-mesh codends and a new square-mesh design made from 20-mm mesh hung on the bar for river and lagoon penaeid seines in south-eastern Australia were compared. The square-mesh design significantly improved the selectivities of the river seine for school prawns, Metapenaeus macleayi (Haswell), and the lagoon seine for greasyback prawns, Metapenaeus bennettae (Racek & Dall), by increasing their carapace length at 50% probability of retention (L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Macbeth et al, 2005) the data suggest that the codends made of diamond-mesh used in the fishery are less selective than the squaremesh codends tested and, since the catches of seabob shrimp were not affected, it should be feasible to use larger sizes of mesh. Further research is required, therefore, to explore the utility of different operational changes in the fishing gear configurations in the fishery.…”
Section: Discussionmentioning
confidence: 99%
“…Macbeth et al, 2005) the data suggest that the codends made of diamond-mesh used in the fishery are less selective than the squaremesh codends tested and, since the catches of seabob shrimp were not affected, it should be feasible to use larger sizes of mesh. Further research is required, therefore, to explore the utility of different operational changes in the fishing gear configurations in the fishery.…”
Section: Discussionmentioning
confidence: 99%
“…This undoubtedly affected mesh-size selectivity. Macbeth (2005) had reported that the presence of weed reduced the L 50 for greasyback prawns caught in the conventional diamond-mesh codend of a lagoon-seine. Mesh clogging could be one an explanation for the negative L 50 differences observed between the comparative and control hadrahs.…”
Section: Resultsmentioning
confidence: 98%
“…One option might be to construct meshes from other types of twine or semi-rigid materials that have minimal elasticity and also maintain their shape (Broadhurst et al, 2006a). Alternatively, the use of square-shaped meshes in the posterior bunt may warrant investigation, since these are less likely to have variable lateral openings during fishing and have been demonstrated to improve selection in a range of towed gears (Suuronen and Millar, 1992;Stergiou, 1999;Macbeth et al, 2005).…”
Section: Discussionmentioning
confidence: 97%